Characterization of Genetic Diversity and Variation in Pathogenicity of the Rice False Smut Pathogen Ustilaginoidea virens from a Single Source - Tan, Ze; Bai, Zhenxu; Qin, Yubao; Du, Jianhang; Zhang, Ruixuan; Tian, Binnian; Yang, Yuheng; Yu, Yang; Bi, Chaowei; Sun, Wenxian; Fang, Anfei (Plant disease, 2022)
Rice false smut, caused by , is one of the most destructive fungal diseases in rice-growing countries. Studies of the genetic diversity, evolution, and pathogenicity of can provide more information for disease control and cultivar breeding. Contrary to previous studies on the genetic diversity of different geographical populations of , in this study the genetic variation of from different panicles of the same rice cultivar in a field in Yunnan province was analyzed using SNP molecular markers. A total of 183 polymorphic loci and five haplotypes, hap_1 to hap_5, were identified based on the 1350-bp combined DNA fragment of 127 isolates, showing some genetic diversity. Hap_1 and hap_3 had the highest occurrence, indicating they were the dominant haplotypes in the field. Further analysis showed that most rice panicles could be co-infected by different haplotypes, and even a few spikelets could be co-infected by multiple haplotypes. The phylogeny indicated that all isolates were divided into five genetic groups. Groups Ⅰ, II, and Ⅲ clustered together and distinguished from Groups Ⅳ and Ⅴ. Significant genetic variations in five pairwise comparisons of panicle populations, accounting for 72.45% of the total variation, were found according to F values. This variation might be caused by different field microenvironments and the uneven distribution of inoculum sources. A UPGMA dendrogram and the population structure revealed that the genetic composition of the isolates collected from YN1, YN2, and YN4, which were dominated by the same genetic subgroup, was different from that collected from YN3. Finally, genetic recombination was found in 11 isolates; hap_2 and hap_5, probably as genetic recombination progenies produced by sexual hybridization between hap_1 and hap_3, acquired a greater virulence than their ancestors according to population structure and pathogenicity analyses. These results will help us understand the genetic diversity, evolution, and infection process of , aiding in the development of more effective management strategies for rice false smut, including new cultivars with improved resistance.